2021
DOI: 10.1002/bit.27754
|View full text |Cite
|
Sign up to set email alerts
|

Microbial ecology in selenate‐reducing biofilm communities: Rare biosphere and their interactions with abundant phylotypes

Abstract: Selenate (SeO 4 2− ) reduction in hydrogen (H 2 )-fed membrane biofilm reactors (H 2 -MBfRs) was studied in combinations with other common electron acceptors. We employed H 2 -MBfRs with two distinctly different conditions: R1, with ample electron-donor availability and acceptors SeO 4 2− and sulfate (SO 4 2− ), and R2, with electron-donor limitation and the presence of electron acceptors SeO 4 2− , nitrate (NO 3 − ), and SO 4 2− . Even though H 2 was available to reduce all input SeO 4 2− and SO 4 2− in R1, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Therefore, a greater density value indicates higher crosstalk among the resident microbes represented in the network nodes ( 35 ). Moreover, network density shows how quickly perturbations may spread ( 51 ). Thus, the small network density ( Figure S4A ) indicated microbial communities composed of scarcely connected groups.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a greater density value indicates higher crosstalk among the resident microbes represented in the network nodes ( 35 ). Moreover, network density shows how quickly perturbations may spread ( 51 ). Thus, the small network density ( Figure S4A ) indicated microbial communities composed of scarcely connected groups.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the thermophilic lifestyle of both cultivated representatives, other members of Ignavibacteria have been detected in a variety of environments: thermal springs in Armenia [5], China [6], USA [7,8] and Russia [9], an anammox membrane bioreactor [10], microbial fuel cells [11], and an upflow anaerobic sludge blanket reactor [12]. Considering the outstanding ability of M. roseus to utilize different electron acceptors, it is interesting to note that members of Ignavibacteria are often detected in sites enriched with iron [13], nitrous [14,15] or sulfur compounds [12], and selenate [16]. In addition, more recent work has shown that the members of Ignavibacteria can play an important role in the degradation of a number of aromatic compounds, such as aniline [17], nitro-and aminophenol [18], or benzoate [19], suggesting their potential involvement in bioremediation.…”
Section: Introductionmentioning
confidence: 99%